The Goddard guide to arthropods of medical importance - Goddard, Jerome II; Moraru, Gail Miriam 1986- (CRC Press, 2019)
Includes an in-depth chapter with diagnostic aids to help physicians to recognize and accurately diagnose arthropod-related diseases and conditions more easily Updates all chapters with the latest medical and scientific findings, including Zika virus, red meat allergy, new viruses found in ticks, and vaccine development for malaria and dengue fever Presents a greater medical parasitology emphasis throughout Offers electronic downloads containing additional photographs of arthropod-caused diseases and lesions, as well as instructional videos with pest identification aids, basic entomology, and insect and pest ecology. Covering all major arthropods of medical importance worldwide, this award-winning resource has established itself as a standard reference for almost 25 years. With the globilization of commerce and the world becoming more intimately connected through the everyday ease of travel, unknown arthropod species are being increasingly encountered. This means access to up-to-date, authoritative information in medical entomology has never been more important. Now in its seventh edition, this book maintains its well-acclaimed status as the ultimate easy-to-use guide to identify disease-carrying arthropods, the common signs and symptoms of vector-borne diseases, and the current recommended procedures for treatment. Illustrated throughout with detailed color images to aid identification, The Goddard Guide to Arthropods of Medical Importance, Seventh Edition will remain an essential guide for physicians, public health officials, and pest control professionals